New Insights into the Theory of Giffen Goods - Heijman, Wim.; Mouche, Pierre von.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
One might expect that after their identification in the 19th century, all aspects of Giffen goods would have been studied by now. This appears not to be the case. This book contains the latest insights into the theory of Giffen goods. In the past, surprisingly few goods could be categorized as (3z(BGiffen.(3y (BThis may be because of a lack of understanding of the character of these goods. Therefore, the theories explained in this book may also produce a solid basis for further empirical research in the field. Experts throughout the world have contributed to this book, which predominantly pursues a mathematically rigorous approach. It may be used by researchers in the field of fundamental economics and in graduate-level courses in advanced microeconomics.s
Introduction -- Notes on Some Theories of Giffen Behaviour -- Exact and Useful Optimization Methods for Microeconomics -- On the Definitions of Giffen and Inferior Goods -- Giffen Behaviour and Strong Assymetric Gross Substituability -- A Child Garden of Concrete Giffen Utility Functions: a Theoretical Review -- On Giffen's Paradox -- Giffen Demand for Several Goods -- Giffen Behaviour Independent of the Wealth Level -- A Class of Indirect Utility Functions Predicting Giffen Behaviour -- Close Substitutes and Upward-Sloping Demand Curves -- Lotteries and the Law of Demand.
Keywords: Mathematical optimization; Economic theory; Microeconomics; Economics; Economic Theory/Quantitative Economics/Mathematical Methods; Microeconomics; Optimization; Electronic books